Towards a Philosophy of Digital Media (Springer International Publishing, 2018)
This book uses the conceptual tools of philosophy to shed light on digital media and on the way in which they bear upon our existence. At the turn of the century, the rise of digital media significantly changed our world. The digitizing of traditional media has extraordinarily increased the circulation of texts, sound, and images. Digital media have also widened our horizons and altered our relationship with others and with ourselves. Information production and communication are still undoubtedly significant aspects of digital media and life. Recently, however, recording, registration and keeping track have taken the upper hand in both online practices and the imaginaries related to them. The essays in this book therefore focus primarily on the idea that digital media involve a significant overlapping between communication and recording. .